A Preoperative Marking Template for Deep Inferior Epigastric Artery Perforator Flap Perforators in Breast Reconstruction - Miranda, Benjamin H; Pywell, Matthew; Floyd, David (Archives of Plastic Surgery, 2014)
Preoperative perforator marking for deep inferior epigastric artery perforator flaps is vital to the success of the procedure in breast reconstruction. Advances in imaging have facilitated accurate identification and preselection of potentially useful perforators. However, the reported imaging accuracy may be lost when preoperatively marking the patient, due to 'mapping errors', as this relies on the use of 2 reported vectors from a landmark such as the umbilicus. Observation errors have been encountered where inaccurate perforator vector measurements have been reported in relation to the umbilicus. Transcription errors have been noted where confusing and wordy reports have been typed or where incorrect units have been given (millimetres vs. centimetres). Interpretation errors have also occurred when using the report for preoperative marking. Furthermore, the marking process may be unnecessarily time-consuming. We describe a bespoke template, created using an individual computed tomography angiography image, that increases the efficiency and accuracy of preoperative marking. The template is created to scale, is individually tailored to the patient, and is particularly useful in cases where multiple potential suitable perforators exist.
Keywords: Free tissue flaps; Perforator flaps; Mastectomy; Breast neoplasms; Tomography, X-ray computed